Understanding the factors that inhibit the success of indigenous entrepreneurs in Malaysia - Amiruddin, Mohd Hasril; Sumarwati, Sri; Madar, Ahmad Rizal; Abdullah, Nurhanim Saadah; Suib, Siti Normah (2020)
This study aims to identify the factors that inhibit the success of indigenous entrepreneurs. The instrument in this quantitative study was a questionnaire that consisted of 54 items with Likert Scale 5. The respondents of this study were 377 indigenous youth entrepreneurs, who were selected by random sampling. Statistical Package for the Social Sciences (SPSS) program version 21 used to analyze data based on frequency, percentage, and linear regression. The results show that there are nine (9) main factors that inhibit the success of indigenous entrepreneurs in Malaysia. Factors that inhibit indigenous from becoming successful entrepreneurs include being lacking financial capital, experience, knowledge in information technology and business strategy, entrepreneurial information, management skills, networking skills, difficulty in finding skilled workers, and complicated financial loan bureaucracy. Factors that inhibit the success of indigenous entrepreneurs classify into two categories. The findings of this study showed that the intrinsic and extrinsic factors had a significant influence on the motivation of Malaysian indigenous youth in entrepreneurship development. Therefore, entrepreneurship and information technology courses are necessary to improve the knowledge and skills of indigenous in Malaysia. However, on the whole, it was found that the bureaucracy of complicated financial lending had become the dominant factor that inhibits the success of indigenous entrepreneurs in Malaysia.